Long-term exposure to PM2.5 exacerbates dopaminergic neuronal loss through CpG hypermethylation induced down-regulation of PINK1 and DJ-1 genes - Xiangnan Du; Longfei Guan; Chen Chen; Xuemei Wang; Xiaokun Geng (Scientific Reports)
Abstract To investigate whether airborne particle (PM2.5) aggravates Parkinson’s disease (PD) and alter expression of key PD-related genes by DNA methylation. Two groups of rats were exposed to either clean air or polluted air for 3, 6, and 12 months. The neurotoxin rotenone was injected intraperitoneally to induce a Parkinson’s-like disorder. Immunostaining was used to measure the number of dopaminergic neurons in substantia nigra (SN). Real-time PCR was used to measure mRNA levels of PD-related genes PINK1 and DJ-1 in SN. Bisulfate sequencing (BSP) was used to measure DNA methylation levels in gene promoters. In a cell-based mimic of animal experiments, SH-SY5Y cells were treated with Diesel exhaust PM2.5 (DEP) for 1.5, 6, and 24 h. RT-PCR and BSP methods were used to measure gene expression and methylation of CpG islands in the cells. Persistent exposure to PM2.5 significantly increased the loss of dopaminergic neurons in the SN. Prolonged PM2.5 exposure and DEP treatment significantly reduced the mRNA levels of PINK1 and DJ-1. Both PM2.5 and DEP significantly increased the methylation level of the CpG islands in both genes. PM2.5 induced loss of dopaminergic neurons and aggravated Parkinson’s disease. PM2.5 induced dysregulation of DNA methylation, resulting in decreased expression of the PINK1 and DJ-1.